Northwest history. Mining. Discovery. 1919-09-06 (1919)
Silver-lead ore found in Banner. Three feet of quartz, with a scattering of silver-lead ore, has been uncovered on the Banner property in the Beaver creek district of the Coeur d'Alenes. The Banner was taken over some time ago by the Sunshine Mining company. Dan McGrath, manager. The strike was made a short distance above the Idora mill on the west side of Carbon creek.